Nuclear DNA level and life cycle of kelps: Evidence for sex‐specific polyteny in Macrocystis (Laminariales, Phaeophyceae). Issue 2 (20th January 2016) - Müller, Dieter G.; Maier, Ingo; Marie, Dominique; Westermeier, Renato
Abstract : Giant kelp, Macrocystis pyrifera (Linnaeus) C. Agardh, is the subject of intense breeding studies for marine biomass production and conservation of natural resources. In this context, six gametophyte pairs and a sporophyte offspring of Macrocystis from South America were analyzed by flow cytometry. Minimum relative DNA content per cell (1C) was found in five males. Unexpectedly, nuclei of all female gametophytes contained approximately double the DNA content (2C) of males; the male gametophyte from one locality also contained 2C, likely a spontaneous natural diploid variant. The results illustrate a sex‐specific difference in nuclear DNA content among Macrocystis gametophytes, with the chromosomes of the females in a polytenic condition. This correlates with significantly larger cell sizes in female gametophytes compared to males and resource allocation in oogamous reproduction. The results provide key information for the interpretation of DNA measurements in kelp life cycle stages and prompt further research on the regulation of the cell cycle, metabolic activity, sex determination, and sporophyte development.